Comparative Evaluation of Ultrasonic Tips and the Masserann Kit for Retrieval of Separated Endodontic Instruments – an in vivo study - Prathapan, Athira; Agrawal, Shyam; Sharma , Deepak; Khan, Babra; Gupta, Ashish; Thakral, Shivam (Journal of Neonatal Surgery, 2025)
Aim:This in vivo study introduces a novel dual-parameter evaluation—dentin preservation and postoperative patient comfort—while comparing ultrasonic tips and the Masserann kit for retrieval of separated endodontic instruments. Materials and Methods:Forty patients (20–60 years) with fractured instruments were randomly divided into two groups: Group 1 underwent retrieval using ultrasonic tips, and Group 2 with the Masserann kit. Residual dentin thickness and postoperative discomfort (Visual Analog Scale, VAS) were recorded. Data were analyzed using the Shapiro–Wilk test, followed by the Mann–Whitney U test. A p-value < 0.05 was considered significant. Results:Ultrasonic tips preserved significantly greater dentin thickness (1.45 ± 0.10 mm) than the Masserann kit (1.03 ± 0.19 mm, p < 0.001). VAS pain scores were lower in the ultrasonic group (1.20 ± 1.20) compared to the Masserann group (2.50 ± 1.61, p = 0.006). Conclusion:This study is one of the first controlled in vivo clinical trials to simultaneously quantify dentin preservation and postoperative comfort in fractured instrument retrieval. Ultrasonic tips proved superior to the Masserann kit, offering a minimally invasive, tooth-conserving, and patient-friendly approach. Clinical Significance:By integrating structural preservation with patient-centered outcomes, this work provides an innovative clinical decision framework—positioning ultrasonic tips as the preferred technique for modern, minimally invasive endodontic practice